2011
DOI: 10.1108/17471111111175173
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between corporate social responsibility and value added intellectual capital: empirical evidence from Turkey

Abstract: PurposeCorporate social responsibility (CSR) has become one of the mainstream issues for sustainable corporate performance in recent decades. Engagement in CSR activities has proven to have certain benefits for companies, ranging from better financial performance to shareholder wealth maximisation. Companies' value creation process has been dominated by companies' hidden assets and concurrently the concept of value added intellectual capital (VAIC). The purpose of this study is to provide evidence from an emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 30 publications
0
32
0
1
Order By: Relevance
“…Finally, the third category of IC has received different definitions by the prior literature. In particular, some authors refer to relational capital (e.g., References [18][19][20]27]), while other adopt the concept of social capital [14,28,51]. Indeed, consistent with Youndt and Snell [14] (p. 338), the two concepts are convergent as social capital [69,70] in organizational and sociological theories is "virtually identical" to what Bontis [53] called relational capital.…”
Section: Ic As a Critical Resource For Firm Performancementioning
confidence: 87%
See 3 more Smart Citations
“…Finally, the third category of IC has received different definitions by the prior literature. In particular, some authors refer to relational capital (e.g., References [18][19][20]27]), while other adopt the concept of social capital [14,28,51]. Indeed, consistent with Youndt and Snell [14] (p. 338), the two concepts are convergent as social capital [69,70] in organizational and sociological theories is "virtually identical" to what Bontis [53] called relational capital.…”
Section: Ic As a Critical Resource For Firm Performancementioning
confidence: 87%
“…Consistent with Pedrini's literature review [18], in the past, several instruments have been adopted to measure and monitor IC. From an accounting-based perspective, a widely used quantitative measure of IC is VAIC, the value-added intellectual capital model (e.g., References [27,31,39,[75][76][77]. In particular, this model was implemented to measure IC efficiency and, thus, the contribution to firm financial performance.…”
Section: Ic As a Critical Resource For Firm Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Although only few have argued that shareholder wealth maximisation should be the focus of an organisation, many concluded that there is some benefit offered by a wider stakeholder interest consideration while some have gone further to place emphasis on considering all relevant stakeholders in decision-making processes. The different perspectives can be generally split into four categories, namely positive effect (Turban & Greening, 1997), negligible albeit positive effect (Aras et al, 2011), neutral relationship (Abbott & Monsen, 1979), and negative effect (Crisóstomo et al, 2011). One aspect that most research consensually agrees upon is the difficulty in the quantification of the CSR-financial performance effect.…”
Section: Theoretical Backgroundmentioning
confidence: 99%